OPERATIONAL EFFICIENCY AND FINANCIAL PERFORMANCE OF MALAYSIAN FAMILY TAKAFUL: A CONCEPTUAL FRAMEWORK IN THE ERA OF DIGITAL TRANSFORMATION - Md Sanusi , Norul Elya Shahira; Hasan , Hazriah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The Family Takaful industry plays a significant role in the Islamic financial system in Malaysia by providing Shariah-compliant protection and long-term financial planning solutions for individuals and families. As the industry continues to expand amid increasing competition, regulatory developments and evolving operational practices, understanding the factors that support sustainable financial performance has become increasingly important. In particular, operational efficiency has emerged as a key organisational capability that influences how effectively Takaful operators utilise resources and manage operational costs to maintain financial stability. However, existing studies often examine financial performance and operational efficiency separately, while the potential role of digital transformation in shaping this relationship remains relatively underexplored. This study aims to develop a conceptual framework that explains the relationship between operational efficiency and financial performance within the Malaysian Family Takaful industry in the context of digital transformation. The study adopts a conceptual research approach by synthesising insights from existing academic literature, industry reports and regulatory publications. The framework is guided by several theoretical perspectives, including efficiency theory, the resource-based view (RBV) and dynamic capability theory, which explain how effective resource utilisation and organisational capabilities can support financial sustainability. The proposed framework conceptualises operational efficiency as a key organisational capability that contributes to improved financial performance through effective cost management, resource utilisation and service delivery. Digital transformation is incorporated as a supporting factor that enhances operational processes through technological adoption, automation and improved data management. The paper concludes that integrating operational efficiency and digital transformation provides a more comprehensive perspective on financial performance dynamics in the Family Takaful industry and offers a conceptual foundation for future empirical research on the long-term sustainability of Takaful operators in Malaysia.